2013
DOI: 10.3389/fneur.2013.00058
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Full Length of the Motor End Plate Regions in the Mouse Forelimb Increases the Uptake of Fluoro-Gold into Corresponding Spinal Cord Motor Neurons

Abstract: Lower motor neuron dysfunction is one of the most debilitating motor conditions. In this regard, transgenic mouse models of various lower motor neuron dysfunctions provide insight into the mechanisms underlying these pathologies and can also aid the development of new therapies. Viral-mediated gene therapy can take advantage of the muscle-motor neuron topographical relationship to shuttle therapeutic genes into specific populations of motor neurons in these mouse models. In this context, motor end plates (MEPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 70 publications
3
45
0
Order By: Relevance
“…We examined the distribution of CST labeling in the C5/C6 segments and the C7/C8 segments. Retrogradely labeled deltoid, biceps, and wrist extensor motoneurons are present throughout these segments ( [22]; see below). Joint-specific sites projected consistently to a dense core region on individual spinal sections (typically a single site; occasionally 1 or 2 additional sites of much lesser density) within a more variable and broad sparsely labeled region (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the distribution of CST labeling in the C5/C6 segments and the C7/C8 segments. Retrogradely labeled deltoid, biceps, and wrist extensor motoneurons are present throughout these segments ( [22]; see below). Joint-specific sites projected consistently to a dense core region on individual spinal sections (typically a single site; occasionally 1 or 2 additional sites of much lesser density) within a more variable and broad sparsely labeled region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the shoulder, we injected the Deltoid muscle group (spino- and acromiodeltoidus). We have optimized the CTb injections to maximally label the motoneurons of injected muscles, taking advantage of recent findings that many forelimb motor pools have an extended rostrocaudal distribution [22].We inserted the Hamilton syringe into the muscle, advanced it along the long axis of the muscle, and injected CTb as the needle was withdrawn. As needed to maximally label the muscle, we often re-advanced the needle and injected more tracer.…”
Section: Methodsmentioning
confidence: 99%
“…We began with a broad sample population of neurons by identifying Golgi-stained ␣-motor neurons located in the ventral spinal cord in Rexed lamina IX and with soma diameters Ͼ25 m (Hashizume et al 1988;Jacob 1998). Above the injury site (C4 -C5), we narrowed candidate neurons for analysis by selecting neurons from motor pools located in similar dorsolateral coordinates of ␣-motor neurons shown to innervate the extensor carpi radialis muscle group (ϳ1.5-2 mm deep, 1.5-2 mm lateral from midline), as we and others have demonstrated through intramuscular retrograde tracing studies (Sunshine et al 2013;Tan et al 2012a;Tosolini et al 2013). Below the injury site (L4 -L5), we narrowed our sampled ␣-motor neurons to those located in ventral motor pools with similar dorsolateral coordinates of motor pools known to innervate the plantar muscle (ϳ1.5-2.5 mm deep, 1.5-2.2 mm lateral from midline) as shown by retrograde tracing (Crockett et al 1987;Jacob 1998).…”
Section: Animals and Spinal Cord Injurymentioning
confidence: 99%
“…Our second approach was to attempt to localize zones of high neuromuscular junction density near the motor end plate using electrical stimulation. Previous rodent studies have demonstrated that targeting muscle injections along motor endplates greatly enhances motor neuron transduction [42,48]. Targeting of the motor end plate as in these studies requires prior histological mapping of the motor end plate in a given muscle in situ followed by visual alignment of anatomical landmarks in the subject to be injected.…”
Section: Virus Delivery Approachesmentioning
confidence: 99%